2020
DOI: 10.2337/dc19-2606
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between HbA1c and Time in Hypoglycemia During CGM and Self-Monitoring of Blood Glucose in People With Type 1 Diabetes and Multiple Daily Insulin Injections: A Randomized Clinical Trial (GOLD-4)

Abstract: According to recent guidelines, individuals with type 1 diabetes should spend <4.0% of time per day with glucose levels <3.9 mmol/L (<70 mg/dL) and <1.0% per day with glucose levels <3.0 mmol/L (<54 mg/dL). RESEARCH DESIGN AND METHODS In the GOLD randomized crossover trial, 161 individuals with type 1 diabetes treated with multiple daily insulin injections (MDI) were randomized to continuous glucose monitoring (CGM) or conventional therapy with self-monitoring of blood glucose (SMBG) and evaluated over 16 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 15 publications
(25 reference statements)
2
27
0
Order By: Relevance
“…This indicates that the wisdom of attempting TIR > 70% should always be evaluated on the background of achieved GMI or mean glucose and TBR. 20 We found a curvilinear relation between TIR and GMI and recognize a similar result from a pediatric population. 21…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates that the wisdom of attempting TIR > 70% should always be evaluated on the background of achieved GMI or mean glucose and TBR. 20 We found a curvilinear relation between TIR and GMI and recognize a similar result from a pediatric population. 21…”
Section: Discussionsupporting
confidence: 86%
“…Even with a less ambitious TIR of 60%, a recent study noticed a corresponding mean TBR of 4.2% for patients with rtCGM and 7.7% for those with SMBG. 20 This underscores the importance of individualized and realistic treatment goals. We are not aware of similar presentations of data for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…For adults who treated with MDIs of prandial and basal insulin or insulin pumps, training should be provided professionally and systematically (NRS, General). All adult T1DM patients should be encouraged to use real-time CGM devices to control blood glucose and lower the risk of hypoglycemia (RCT, General) [ 135 - 137 ]. Adults with T2DM who require MDIs may use realtime CGM devices for glycemic control (RCT, Limited) [ 138 ].…”
Section: Cgm System and Insulin Pump Usementioning
confidence: 99%
“…For these reasons, despite improvements in the diagnosis and treatment of diabetes, exposure to hypoglycaemia remains the most feared consequence of insulin treatment. The recent GOLD‐4 clinical trial reported that individuals with Type 1 diabetes and average blood glucose of 8 mmol/L spend 12% of their time below 3.9 mmol/L and 4.9% below 3 mmol/L 9 . Plasma blood glucose was measured using self‐monitoring blood glucose meters or continuous glucose monitors (CGM).…”
Section: Defective Counterregulatory Response To Hypoglycaemia In Type 1 Diabetesmentioning
confidence: 99%
“…Plasma blood glucose was measured using self‐monitoring blood glucose meters or continuous glucose monitors (CGM). Time spent in the hypoglycaemic range was reduced in individuals with higher average blood glucose and those using CGM 9 . Non‐severe hypoglycaemia is estimated to occur twice weekly in people with Type 1 diabetes, whereas episodes of severe hypoglycaemia are predicted to occur between 1 and 3 annually in a large proportion of those with Type 1 diabetes 4,10 .…”
Section: Defective Counterregulatory Response To Hypoglycaemia In Type 1 Diabetesmentioning
confidence: 99%